THE EFFECTS OF RUM WONG MATRATAN PROGRAM ON MAXIMAL OXYGEN CONSUMPTION IN FEMALE STUDENTS IN UDON THANI RAJABHAT UNIVERSITY - Thonglong, Thanumporn; RATTANATHANTONG, Korawan; CHAISRI, Patcharaporn (Journal of Sports Science and Technology, 2019)
The objective of this quasi-experiment research was to study the effect of Rum Wong Matratan exercise program to maximum oxygen consumption of female students, Udon Thani Rajabhat University. The samples group applying the purposive sampling method consisted of 24 females in Udon Thani Rajabhat University. The sample divided into 2 groups with each group consisting of 12 similarly subjects; control group and experimental group. The experimental group was given 14 Rum Wong Matratan exercise program with duration a 8 weeks. The personal questionnaire was collected and a maximum oxygen consumption was determined by using one-mile walk test. All parameters were measured before, after the 4th week and after the 8th weeks, respectively. The data were analyzed by using percentage, mean, standard deviation, t - test and One-way analysis of variance with repeated measure. Scheffe was compared at the statistical significance level at p<0.05. The results showed that the estimate VO2 max of control group and experimental group after training on week 8th were significantly different at p<0.05. This research suggest that Rum Wong Matratan program training for 8 weeks can improves the maximum oxygen consumption. (Journal of Sports Science and Technology 2019; 19(1): 58-68) (Received: 3 December 2018, Revised: 20 January 2019, Accepted: 14 February 2019) Keywords: Rum Wong Matratan / Maximum oxygen consumption / Female student *Corresponding author: Thanumporn THONGLONG Sports Science Program, Faculty of Science, Udon Thani Rajabhat University, Mueang Udon Thani, Udon Thani, Thailand 41000. E-mail: e_pi_@hotmail.com